Does foreign direct investment successfully lead to sustainable development in Singapore? - Abdul Rahim Ridzuan; Nor Asmat Ismail; Abdul Fatah Che Hamat (Economies, 2017)
The role of foreign direct investment (FDI) inflows is tested on three main pillars of sustainable development (SD), which consists of economic growth, income distribution and environmental quality for Singapore. The analysis is performed by using Autoregressive Distributed Lag (ARDL) estimation technique. The sample data is based on annual data, covering the period from 1970 to 2013. The estimated long-run elasticity indicated that FDI inflows not only lead to higher economic growth and better environmental quality but also widen the income disparity in this country, which may disrupt its SD mission. The other two introduced variables that could also play a part as potential drivers for sustainable development (SD) are trade openness (TO) and financial development (FD). Based on the outcomes, TO has also led to higher economic growth and lower environmental degradation. However, this variable does not have significant impact on income distribution for Singapore. As for FD, it is found to have a significant and positive impact on economic growth and also successfully reduce the income inequality problem. On the contrary, this variable does not have any significant relationship with environmental quality, as indicated by carbon dioxide (CO2) emissions. Mixed evidence of a relationship is detected for other macroeconomic variables in the three estimates models. As the income inequality issue has become more serious, it is important for Singaporean policymakers to focus on attracting more foreign investors to invest in various sectors, in the hope that these companies can offer better wages to the local workers and thus improve income distribution in the country. More attention is needed to explore the potential role of TO and FD as drivers for SD in this country.
Keywords: F18; F62; F63; 330; sustainable development; foreign direct investment; trade openness; financial development